PRESBYTERIAN CHURCH IN TAIWAN (PCT) IN DIASPORA - Chen, Tsung Yuan (Asia Pacific Journal of Religions and Cultures, 2025)
The geography of religion is a branch of cultural geography (Bottiglioni, 1954; Levine, 1986; Mcdavid Jr, 1986; Park, 2005). Since the 1980s, relevant research in Taiwan has focused mainly on the traditional religious sphere, lacking studies on foreign religions and the relationship between religions and languages. This study believes that language and religion are closely related. The primary reason for the Presbyterian Church in Taiwan’s (PCT) use of Taiwanese as its mission language at the initial period of its missionary work was that most people in Taiwan at that time did not know Han characters. After teaching them simple Roman scripts, they could read the Romanized Bible. However, following the end of World War II in 1945, Taiwan was ruled by the Kuomintang (KMT), and the language had been changed from Japanese and Taiwanese to Mandarin. The language policy in the 1970s even prohibited the use of Taiwanese. Since PCT continued to use Taiwanese, it had become a language island in Taiwanese society, which in turn affected its religious situation.